As certain as debt and taxes: Estimating the tax sensitivity of leverage from state tax changes - Heider, Florian; Ljungqvist, Alexander (Journal of Financial Economics, 2015)
Using staggered corporate income tax changes across U.S. states, we show that taxes have a first-order effect on capital structure. Firms increase leverage by around 40 basis points for every percentage-point tax increase. Consistent with dynamic tradeoff theory, the effect is asymmetric: leverage does not respond to tax cuts. This is true even within-firm: tax increases that are later reversed nonetheless lead to permanent leverage increases. The treatment effects are heterogeneous and confirm the tax channel: tax sensitivity is greater among profitable and investment-grade firms which respectively have a greater marginal tax benefit and lower marginal cost of issuing debt.